High proportion of mutant K-ras gene in pancreatic juice of patients with pancreatic cystic lesions. Issue 5 (1st November 1999) - Tateishi, K; Tada, M; Yamagata, M; Isayama, H; Komatsu, Y; Kawabe, T; Shiratori, Y; Omata, M
Abstract : BACKGROUND/AIMS: It was recently reported that the quantitative analysis of mutant K- ras gene in pancreatic juice could be useful for the diagnosis of pancreatic cancer. This methodology was applied to patients with pancreatic cystic lesions. METHODS: DNA was extracted from pancreatic juice collected at the time of endoscopy with injection of secretin. The ratio of the K- ras mutant allele to the wild-type allele was measured by two methods to detect and semiquantify mutant K- ras gene: polymerase chain reaction/preferential homoduplex formation assay and enriched polymerase chain reaction/enzyme linked mini-sequence assay. RESULTS: A high frequency of K- ras mutation was detected (more than 2% of all K- ras genes) in six of 14 patients (43%) with pancreatic cysts. This frequency was similar to those detected in patients with pancreatic adenocarcinoma and in intraductal papillary neoplasms of the pancreas. In contrast, the frequency of mutation was low (less than 2%) in patients without either pancreatic cysts or pancreatic neoplasms. CONCLUSIONS: K- ras gene mutation may be derived from duct cells in the pancreas with a high potential for tumorigenesis. Therefore careful follow up of patients with a pancreatic cyst is recommended if they are found to have a high level of the mutant gene in the pancreatic juice.